Phosphate Adsorption from Aqueous Solution by &ITLaminaria japonica&IT-Derived Biochar-Calcium Alginate Beads in a Fixed-Bed Column: Experiments and Prediction of Breakthrough Curves - Jung, Kyung-Won; Jeong, Tae-Un; Choi, Brian Hyun; Kang, Ho-Jeong; Ahn, Kyu-Hong (WILEY, 2017)
Phosphate adsorption onto Laminaria japonica-derived biochar (LB )-calcium alginate beads (CAB ) under a continuous flow fixed-bed column condition was investigated by varying three operating parameters including the bed height, initial phosphate concentration, and flow rate. Experimental results confirm ed that the breakthrough time and exhaustion time decreased with decreasing bed height and increasing initial phosphate concentration and flow rate. The relation ship between the adsorption capacity of LB-CAB and, the varied parameters was assessed and, predicted using three different theoretical breakthrough curve models: the Adams-Bohart, Thomas, and Yoon-Nelson models. Among them, the breakthrough curves were successfully simulated with the Yoon-Nelson model for all operating parameters with the highest R-2 and the lowest error function values. Finally, a simple pot experiment for the growth of Lactuca sativa, revealed that the addition of phosphate adsorbed LB-CAB (10% wt/wt) offers potential for use as an additive to fertilizers for improved soil fertility. (C) 2017 American Institute of Chemical Engineers
Keywords: ACTIVATED CARBON; MARINE MACROALGAE; METHYLENE-BLUE; FRESH-WATER; PACKED-BED; REMOVAL; SORPTION; PB(II); CHROMIUM; EXCHANGE